Sistem Informasi Absensi dan Penjadwalan Kegiatan Organisasi Berbasis Web Menggunakan Metode Agile: Studi Kasus Himasi UIN Suska Riau - Zacky, M.; Mahdi, Taufiq; Mayumi, Farah; Baguno, Nanda Kito; Alghifari, M. Najmi; Hamzah, Muhammad Luthfi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Attendance is a record of individual attendance in an organization, while activity scheduling plays an important role in managing activities. The Information Systems Study Program at the Faculty of Science and Technology of the Campus located in Riau Province has a student organization called the Information Systems Student Association (HIMASI) which functions as a forum for academic development, interests, and competencies of students in the Information Systems Study Program through the implementation of activities that support the improvement of technical skills, soft skills, and professionalism in the field of information technology. Based on observations and interviews conducted, obstacles were found in attendance and activity scheduling in the organization. Both processes are still carried out manually, causing irregularities, delays, and recording errors. The purpose of this study is to create a web-based attendance and activity scheduling information system using the Agile approach to improve the accuracy, transparency, and efficiency of organizational management. The tools used include UML modelling, Visual Studio Code editor, PHP–MySQL as a web development technology, and Black Box Testing as a functional testing tool. The system developed includes digital attendance, centralized scheduling, member data management, and automatic notifications. Testing results show that the six main modules are Login, Dashboard, HIMASI Data, Member Data, Reports, and Logout. The success rate is. The tools used include UML modelling, Visual Studio Code editor, PHP–MySQL as web development technology, and Black Box Testing as a functional testing tool. The system developed includes digital attendance, centralized scheduling, member data management, and automatic notifications. The test results show that there are six main modules: Login, Dashboard, HIMASI Data, Member Data, Reports, and Logout. The success rate is calculated from the number of successful modules (6 modules) divided by the number of modules tested (6 modules), then multiplied by 100%, so that the testing success rate reaches 100% with no errors found. User responses also show an increase in the ease of online attendance, access to information, and real-time activity reminders. This study proves that the Agile method is effective in overcoming manual system problems and producing a structured, efficient, and easily developed platform to support organizational governance. This study is useful in improving the efficiency of attendance management and organizational scheduling, as well as providing a basis for developing a more integrated system. Further research is recommended to add mobile features, app-based notification integration, and large-scale testing to make the system more adaptive and sustainable.